The effect of plant density on maize yield in average and extremely dry years - Boros, Beáta; Sárvári, Mihály (Acta Agraria Debreceniensis, 2008)
The yield safety of maize has not been satisfactory in Hungary for decades. Yield is influenced by the combination of several factors. In recent years, the frequency of dry years increased and fertilization decreased. These factors call for a rational determination of the plant density. I studied the relationship between plant density and yield in 2003-2004 and 2007 on meadow soil. In 2003, the weather was dry. In the vegetation period, the amount of precipitation was 78.5 mm lower and the temperature was 0.97 °C higher than the average of 30 years, the number of hot days was 47-60 (days with a temperature higher than 30 °C). However, we obtained favourable results under experimental conditions in 2003 after wheat as a forecrop using the fertilizer Kemira Power. The weather in 2004 was favourable. In the vegetation period, the amount of precipitation was 93.2 mm higher than the average of 30 years. Although, the distribution of the precipitation could have been more favourable. The yield of the hybrids ranged between 8.87-10.42 t/ha. Among the studied seven hybrids, the early hybrids gave the highest yield at the highest plant density of 90 thousand plants/ha (PR38Y09, PR38A67, PR37D25, PR37M34). However, FAO 400-500 hybrids gave favourable results also at the low plant density of 45 thousand plants/ha (8-9 t/ha). At this plant density, the aeration of the plant stock was better and the hybrids were prone to bringing several cobs. Yield stagnated with increasing plant density (60 thousand plants/ha), then at 75-90 thousand plants per ha, the yield started to increase again. In 2004 the yield of hybrids was considerably higher than in the previous year. In contrast to yields of 8.87-10.42 t/ha in 2003, yields in 2004 were around 9-12 t/ha. The yield of the hybrid XO 902 P is above 12 t/ha already at a plant density of 45 thousand plants/ha. It gives maximum yield at the plant density of 90 thousand plants/ha. The hybrid PR38P92 showed a good response to changing plant density, but its yield was only 9 t/ha at the low plant density value. In a favourable year, the yield of the hybrids PR38B85, PR37W05, PR37D25, PR37K85 at a plant density of 45 thousand plants/ha 11 t/ha, while at the higher plant density of 90 thousand plants/ha, it ranges around 13-15 t/ha. Hybrids PR36K20, PR35Y54, PR34H31 have a good individual yield and they are prone to bringing several cobs in favourable years at a low plant density. Their maximum yield at the plant density of 90 thousand plants/ha is almost 16 t/ha. In 2007, the weather was similar to that of the extremely dry year of 2003. The amount of precipitation in the vegetation period was 41.9 mm lower than the average of 30 years and its distribution was not favourable either. In the optimum NPK fertilizer treatment at an optimum plant density, the yield of hybrids ranged between 9.32-10.73 t/ha. The highest yields of 10.22-10.73 t/ha were measured for hybrids PR38A79 (FAO 300) and PR35F73 at a relatively low plant density of 60 thousand plants/ha. In the average of the hybrids, the optimum NPK dosage was N 131, P2O5 82, K2O 93 kg/ha active ingredient.